The competitive challenge : - Teece, David J. (Ballinger Pub. Co., 1987)
This book is a collection of lectures presented at the School of Business, niversity of California, Berkeley, of the erica chair in corporate strategy. The lectures were initially presented revised and academic year 1984-85 but in most cases were subsequently extended. The generous support of the ration in endowing the chair and permitting the funds to be used to support the lectures is gratefully acknowledged......